ALTERNATIVE DISPUTE RESOLUTION IN CREDIT AGREEMENTS IN THE BANKING SECTOR - Marihot Manurung, Fam Kelvin; Hendrawan, Daniel (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
This research aims to find out the alternative settlement of bad credit disputes over the deed of granting mortgage rights. In principle, someone who wants to borrow money from a bank must have sufficient collateral to guarantee his debt. Mortgage rights on land are given as collateral for one's debt, in the form of encumbrance on land rights and objects that are legally integrated with the land. Not all loans banks provide borrowers can be repaid fully under the agreement. Poor credit repayment from debtors can be due to carelessness, lack of good faith, or due to their incompetence. To prevent losses for the lending bank so that debtor customers can continue paying their obligations. This study aims to identify alternative methods of resolving conflicts of mortgage rights related to bad credit. The author uses a normative juridical approach method by referring to the legal standards applicable in Indonesia. In order to analyze the existing problems, normative juridical analysis is the method used. Bad credit disputes that affect the granting of mortgage rights can be resolved through alternative dispute resolution. Compared to litigation, alternative dispute resolution can result in a significant settlement of bad credit by prioritizing a win-win solution where the parties' free will is maintained.